2011
DOI: 10.1371/journal.pone.0021693
|View full text |Cite
|
Sign up to set email alerts
|

Mink Farms Predict Aleutian Disease Exposure in Wild American Mink

Abstract: BackgroundInfectious diseases can often be of conservation importance for wildlife. Spillover, when infectious disease is transmitted from a reservoir population to sympatric wildlife, is a particular threat. American mink (Neovison vison) populations across Canada appear to be declining, but factors thus far explored have not fully explained this population trend. Recent research has shown, however, that domestic mink are escaping from mink farms and hybridizing with wild mink. Domestic mink may also be sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
61
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 30 publications
(31 reference statements)
8
61
2
Order By: Relevance
“…The disease occurs in wild and domesticated mink (Bloom et al 1994;Nituch et al 2011Nituch et al , 2012, and has been reported in many jurisdictions where domestic mink are raised; it is apparent that the commercial trade of domestic mink contributes to the spread of the virus (Bloom et al 1994;Nituch et al 2012). Aleutian mink disease virus can be highly prevalent in wild mink populations (Nituch et al 2011;Farid 2013) and mink farms can be point sources of disease (Nituch et al 2011), but the extent to which wild and domestic mink transmit AMDV, and other wildlife act as reservoirs, is unknown (Nituch et al 2012;Farid 2013). …”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The disease occurs in wild and domesticated mink (Bloom et al 1994;Nituch et al 2011Nituch et al , 2012, and has been reported in many jurisdictions where domestic mink are raised; it is apparent that the commercial trade of domestic mink contributes to the spread of the virus (Bloom et al 1994;Nituch et al 2012). Aleutian mink disease virus can be highly prevalent in wild mink populations (Nituch et al 2011;Farid 2013) and mink farms can be point sources of disease (Nituch et al 2011), but the extent to which wild and domestic mink transmit AMDV, and other wildlife act as reservoirs, is unknown (Nituch et al 2012;Farid 2013). …”
mentioning
confidence: 99%
“…Conversely, AMDV could spread from mink farms into the wild via the escape of infected individuals from farms, or through contact between wildlife and infected material on farms. For example, wildlife may visit composting mink carcasses or mink manure piles on farms (Nituch et al 2011). The virus can survive for more than 2 yr in soil and improperly composted manure or carcasses (Bloom et al 1994).…”
mentioning
confidence: 99%
See 3 more Smart Citations